A comparative study of the efficacy of whether or not to preserve the joint capsule during PLIF surgery in patients with isthmic spondylolisthesis - Mi, Jian; Xu, Li; Yang, Peng; Fang, Tian-ci; Ni, Li; Yang, Hui-lin; Zhou, Quan; Zhou, Feng (Frontiers in Surgery, 2025)
PurposeThe purpose of this study is to investigate the effect of joint capsule preservation during posterior lumbar interbody fusion (PLIF) on postoperative low back pain and long-term adjacent segment stability in isthmic spondylolisthesis (IS) patients.MethodsGroup A: Forty-one patients received PLIF without preserving the joint capsule. Group B: Forty patients received PLIF with preserving the joint capsule. This study was randomly assigned, in which eligible patients were assigned to either group A (with joint capsule preservation) or group B (without joint capsule preservation). The radiographic outcomes were assessed via the lumbar lordosis (LL), segmental lordosis (SL), sacral slope (SS), pelvic incidence (PI), pelvic tilt (PT). The functional outcomes were evaluated via the Visual Analog Scale (VAS), Oswestry disability index (ODI), and reoperation rate. Metrics that describe the rate of degradation of adjacent segments include: the height of vertebral interval and the height of the upper intervertebral disc.ResultsThe sagittal balance parameters of the spine in the two groups were significantly improved after PLIF compared with those before surgery (p < 0.05). Compared with group A, the results of PI and PT in group B were significantly better than those in group A during the last follow-up (p < 0.05). Although the height of the upper intervertebral disc and vertebral interval did not show statistically significant results after surgery (p > 0.05), the height showed statistical differences during the last follow-up (p < 0.05).ConclusionsFor patients with IS, we recommend that appropriate patients with IS should preserve the joint capsule as much as possible during PLIF, which is very helpful in preventing long-term degeneration of adjacent segments.